Effect of prednisolone therapy on monocyte phenotype and function in alcoholic hepatitis. (25th February 2016) - Vergis, Nikhil; Khamri, Wafa; Gill, Upkar S; Blackmore, Laura J; Shawcross, Debbie L; Ma, Yun; Antoniades, Charalambos G; Thursz, Mark R
Abstract: Background: Alcoholic hepatitis is characterised by severe hepatic inflammation and is associated with high mortality. Monocytes are pivotal mediators of innate immunity and are described as three subsets in peripheral blood: classical CD14+16–, intermediate CD14+16+, and non-classical CD14lo16+ monocytes. Prednisolone improves liver function at 28 days but is also associated with serious infections that could explain the lack of survival benefit from this drug at 90 days. We aimed to assess the effect of prednisolone therapy on monocyte phenotype and function in alcoholic hepatitis. Methods: Blood samples from 27 patients with alcoholic hepatitis, nine patients with alcohol-related liver cirrhosis, and 46 healthy controls were analysed by flow cytometry. Monocytes were identified from whole blood using monoclonal antibody to CD14 and CD16. Paired longitudinal samples were obtained from 20 of the patients with alcoholic hepatitis who were treated by random allocation in the STOPAH trial. After unmasking, these 20 patients were subdivided into those who had been treated with prednisolone and those who had been treated without prednisolone. Findings: Before therapy, there was a relative monocytosis in patients with alcoholic hepatitis compared with those with alcohol-related liver cirrhosis and controls (median 0·96 × 10 9 /L [IQR 0·6–1·2] vs 0·70 [0·6–0·8] vs 0·5 [0·4–0·7], p=0·003). In particular, the frequency of intermediate monocytes was increased (0·10 × 10 9 /L [·04–0·24] vs 0·11 [0·05–0·15] vs 0·02 [0·015–0·036], p<0·0001). Intermediate monocytes from patients with severe alcoholic hepatitis had increased expression of the activation marker HLA-DR compared with those from patients with alcohol-related liver cirrhosis (11 811 median fluorescence intensity [MFI] [7821–17 694] vs 5848 [3752–8410], p=0·005), produced more tumour necrosis factor (TNF) α (419 [319–1499] vs 263 [195–1527], p=0·03), and expressed higher levels of chemokine receptor CCR5 (516 [227–870] vs 177 [133–281], p=0·01). Importantly, treatment with 7 days of prednisolone led to a reduction in proportion of intermediate monocytes (15% [9–28] reduced to 12 [4–15] in prednisolone treated patients, p=0·05), a finding that was not seen in patients treated without prednisolone. Similarly, activation marker HLA-DR was reduced in patients treated with 7 days of prednisolone compared with patients treated without prednisolone (loss of 8376 MFI [17 247–3990] vs gain of 1836 [–9958 to 4534], p=0·06). Interpretation: Before therapy, intermediate monocytes in alcoholic hepatitis show an activated phenotype that generates more TNFα than classical monocytes. Subsequently, 7 days of prednisolone treatment reduces the number and activation of intermediate cells, which might explain the improved liver function seen with this therapy. Elevation of chemokine receptor CCR5 on the surface of these intermediate monocytes offers a selective target to prevent hepatic infiltration of inflammatory cells, potentially sparing patients the infectious complications of prednisolone. Funding: Wellcome Trust.